High-pressure liquid phase hydroconversion of heptane/nonane mixtures on Pt/H-Y zeolite catalyst - Denayer, Joeri F.M.; Ocakoglu, Refik A.; Huybrechts, Ward; Dejonckheere, Bruno; Jacobs, Pierre; Calero, Sofia; Krishna, Rajamani; Smit, Berend; Baron, Gino V.; Martens, Johan A. (Journal of catalysis, 2003)
The competitive hydroconversion of heptane and nonane molecules in their mixture was studied in a continuous flow, fixed-bed reactor filled with Pt/HY zeolite catalyst. Liquid-phase reaction conditions were established at reaction temperatures of 230, 250, and 270 °C by pressurizing the reactor at 100 bar. Hydrogen was supplied in an absorbed state with the liquid hydrocarbon feed. Under these liquid-phase reaction conditions, the apparent reaction rates of heptane and nonane were almost identical. In a similar experiment under vapor-phase conditions, nonane was much more reactive than heptane. The conversion data under liquid-phase conditions were analyzed with an adsorption-reaction model based on intrinsic kinetic parameters obtained from vapor-phase experiments. The model revealed that the enhanced reactivity of heptane in the liquid phase was due to its preferential adsorption. Simulation of the adsorption of the heptane/nonane mixture in the pores of zeolite Y with the configurational-bias Monte Carlo method confirmed the preferential adsorption of heptane in zeolite Y at high pressure. Under such conditions, in zeolite Y supercages the packing of the smaller heptane molecules is more favorable than that of the larger nonane molecules.